(untitled) (Research, Society and Development, 2023)
The main objective of this research was to analyze the methods of investigating and monitoring characteristics of postural alignment and factors related to postural deviation that contribute to changes in the posture of children and adolescents, as well as the contributions of obesity, growth and inactivity. As a way to continue the study, the systematic and exploratory bibliographic review methodology was used. 9 articles published from 2013 to 2023 were analyzed, selected from the VHL database, Embase, PubMed, Scielo, Google Scholar and Scientific Journals, resulting from the descriptors: Body Posture, Children, Adolescents, Anthropometric Assessment, Educational Assessment. Articles focused on evaluation methods that are commonly used and methods that can be used or inserted were analyzed for professionals to evaluate this public in public schools. From the main results found, it was possible to examine that BMI is the most used method in schools, but other methods such as the Physical Activity Questionnaire for Children (PAQ-C), Symmetrography, Panoramic X-rays, Computerized Dynamic Posturography, Assessment Form Nieman’s postural analysis, Digital Photogrammetry, for example, were also much more efficient for this analysis and monitoring of the postural health of children and adolescents, in addition to the associations of these methods that in the research carried out show promise. Therefore, the combination of these assessment methods could easily be adopted in schools, due to the simplicity of the material used. Furthermore, this study also identified the lack of research focused on these characteristics, helping to elucidate the connection and contributions between physical activity, posture and knowledge of the general functioning of the body in this age group.